2014
DOI: 10.1371/journal.pone.0102135
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Resistance of Mycobacterium tuberculosis to Bedaquiline

Abstract: Bedaquiline (BDQ), an ATP synthase inhibitor, is the first drug to be approved for treatment of multi-drug resistant tuberculosis in decades. In vitro resistance to BDQ was previously shown to be due to target-based mutations. Here we report that non-target based resistance to BDQ, and cross-resistance to clofazimine (CFZ), is due to mutations in Rv0678, a transcriptional repressor of the genes encoding the MmpS5-MmpL5 efflux pump. Efflux-based resistance was identified in paired isolates from patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
325
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(358 citation statements)
references
References 24 publications
17
325
2
Order By: Relevance
“…The demonstration of co-occurrence of canonical mutations in drug target genes and MICs that decrease in the presence of an efflux pump inhibitor, as well as recent studies in clinical isolates, seem to support this new idea. 6,197,198,[199][200][201] Some phylogenetic lineages of M tuberculosis (genotypes) and the strains of these lineages have greater propensity to cause acquired drug resistance-this theory has been especially recognised since the Beijing strain started gaining notoriety in the MDR tuberculosis epidemic. 202 Ford and colleagues 203 did Luria-Delbrück fluctuation analysis on a panel of laboratory and clinical isolates from lineage 2 and lineage 4, to which the Beijing strain belongs, and found the number of mutants per cell plated in a single culture ranged from 2·42 × 10 − ⁹ for the CDC-1551 strain (lineage 2) to 1·94 × 10 − ⁸ for the HN878 strain (lineage 4), which was a significant difference.…”
Section: The Role Of Efflux Pumps In Antibiotic Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…The demonstration of co-occurrence of canonical mutations in drug target genes and MICs that decrease in the presence of an efflux pump inhibitor, as well as recent studies in clinical isolates, seem to support this new idea. 6,197,198,[199][200][201] Some phylogenetic lineages of M tuberculosis (genotypes) and the strains of these lineages have greater propensity to cause acquired drug resistance-this theory has been especially recognised since the Beijing strain started gaining notoriety in the MDR tuberculosis epidemic. 202 Ford and colleagues 203 did Luria-Delbrück fluctuation analysis on a panel of laboratory and clinical isolates from lineage 2 and lineage 4, to which the Beijing strain belongs, and found the number of mutants per cell plated in a single culture ranged from 2·42 × 10 − ⁹ for the CDC-1551 strain (lineage 2) to 1·94 × 10 − ⁸ for the HN878 strain (lineage 4), which was a significant difference.…”
Section: The Role Of Efflux Pumps In Antibiotic Resistancementioning
confidence: 99%
“…A comprehensive list of these mutations is provided in table 4. 199,222,76,[223][224][225]77 Summary of the rise in drug-resistant tuberculosis New efforts have been made to establish how acquired drug resistance and MDR tuberculosis arise in patients Preclinical studies, prospective clinical studies, and metaanalyses have not identified the role of adherence in acquired drug resistance, contrary to common beliefs. Pharmacokinetic variability has emerged as an important proximate cause of acquired drug resistance in vitro, in mathematical simulations, in prospective clinical studies, and in meta-analyses.…”
Section: Mutations Identified By Whole-genome Sequencing That Are Assmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, mutations in the 530 loop and 915 region of rrs gene are associated with streptomycin resistance (Sreevatsan et al., 1996), while mutations in the 1400—1500 region are linked to resistance to kanamycin, amikacin and capreomycin (Jugheli et al., 2009). In particular, cross‐resistance phenomena (Box 1) have also been described in M. tuberculosis (Andries et al., 2014; Jugheli et al., 2009; Vilcheze & Jacobs, 2014). …”
Section: Characteristics and Diversity Of Drug Resistance‐associated mentioning
confidence: 99%
“…ANDRIES et al [19] reported that non-target-based resistance to bedaquiline and cross-resistance to clofazimine are due to mutations in Rv0678. Efflux-based resistance was identified in paired isolates from patients treated with bedaquiline as well as in mice, in which it was confirmed to decrease bactericidal efficacy.…”
Section: New Discoveries: Cross Resistance Between Clofazimine and Bementioning
confidence: 99%